(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
This paper aims to analyze the origins of criminal organizations in the Balkan states, addressing particular attention to the relationship between wars and organized crime. The study aims, first and foremost, to show the impact of the conflicts which led to the dissolution of Yugoslavia in the 1990s, in the growth of Balkan criminal organizations. To this end, the study highlights the role played by paramilitary militias and small criminal gangs all along the war fronts. This is particularly evident in the management of arms smuggling and drugs trafficking routes, thanks to the frequent support of corrupt political elites. Lastly, the essay shows the development of criminal organizations in the Balkans in the period after the Yugoslavian war, which provided fertile ground for criminal expansion in the entire Balkan area. The conclusion underlines the strategic relevance achieved by the former members of the paramilitary groups who became the main leaders of the various criminal organizations, many of whom are still active today.